Monolithically integrated laser with DBR for wideband and low time delay signature chaos generation - Li, Shuhui; Qiao, Lijun; Chai, Mengmeng; Zhang, Mingjiang (Frontiers in Physics, 2023)
A monolithically integrated laser with distributed Bragg reflector (DBR) is designed to address the problem of chaotic laser with periodicity and narrow bandwidth. This proposed chaotic laser consists of a distributed feedback (DFB) laser section, a phase section and a DBR section. DBR grating can provide wavelength detuning to generate mode beating which enhances chaotic bandwidth and distributed feedback to suppress time delay signature (TDS). The transmission line laser model (TLLM) of chaotic laser is constructed by simulation, and chaotic characteristics of the integrated chip are investigated. A chaotic signal with bandwidth of 12.34 GHz and TDS less than 0.065 is obtained. In addition, map of dynamic states in the parameter space of phase section current IP and DBR section current IDBR is depicted, and a wide range of chaotic regions are obtained in suitable parameter space. The effects of IDBR and DBR grating coupling coefficient κ on the chaotic bandwidth are further investigated. The results show that the broadband chaotic laser with low TDS can be obtained by controlling the parameters reasonably, which is beneficial to realize the application of chaotic laser.